55.2k views
1 vote
X+y=7
2x-y=5
Using substitution

2 Answers

1 vote

Answer:

X=4 Y=3

Explanation:

Step: Solvex+y=7for x:

x+y=7

x+y+−y=7+−y(Add -y to both sides)

x=−y+7

Step: Substitute−y+7forxin2x−y=5:

2x−y=5

2(−y+7)−y=5

−3y+14=5(Simplify both sides of the equation)

−3y+14+−14=5+−14(Add -14 to both sides)

−3y=−9

−3y

−3

=

−9

−3

(Divide both sides by -3)

y=3

Step: Substitute3foryinx=−y+7:

x=−y+7

x=−3+7

x=4(Simplify both sides of the equation)

User Wilfred
by
4.7k points
2 votes

Answer: x

=

2

y

=

3

Explanation:

You can re-arrange equation

x

+

y

=

5

to get

x

=

5

y

and then substitute this into the equation

2

x

+

y

=

7

to get

2

(

5

y

)

+

y

=

7

.

This can then be simplified to

10

y

=

7

and so

3

y

=

0

which means

y

=

3

.

Substitute

y

=

3

into

x

+

y

=

5

and you get

x

+

3

=

5

, therefore:

User Enyra
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.